The Potential of Nyamplung Seed Oil (Calophyluminophyllum L.) as a Source of Natural Antioxidants - Liya Fitriyana; Muhammad Dani Supardan; Yuliani Aisyah; Irfan Irfan (Universitas Serambi Mekkah, 2022)
Indonesia has many plants that have the potential as raw materials for medicines and cosmetics, one of which is Calophylluminophyllum which in Indonesian is called the Nyamplung plant. Nyamplung seeds have a high oil content of 73% and have the potential as a source of active compounds. In this study, we looked at the content of active compounds as antioxidants from Nyamplung seed oil produced from the press and press process with degumming. The resulting Nyamplung seed oil contains compounds from the phenolic and steroid groups. Component analysis showed that Nyamplung seed oil contained as many as 20-25 compounds with the highest content being cis-13-Octadecenoic acid, Octadecanoic acid, n-Hexadecanoic acid, cis-Vaccenic acid. Nyamplung seed oil has potential as a source of antioxidants because it has an IC50 value of 50 µg/mL, namely 41.37 µg/mL for oil from the press process and 46.59 µg/mL for oil from the press process with degumming. Keywords: Nyamplung Seed Oil, Extraction, Degumming, Antioxidants